Income and out-of-pocket health expenditure in living arrangements of families with older adults in Brazil - Christine Grutzmann Faustino; Renata Bertazzi Levy; Daniela Silva Canella; César de Oliveira; Hillegonda Maria Dutilh Novaes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: The main objective of this study was to characterize household sociodemographic and economic patterns of different living arrangements of families with older adults in Brazil and their relationship with income and out-of-pocket health expenditure. Data were extracted from the 2008-2009 Brazilian Household Budget Survey (POF, in Portuguese) database of the Brazilian Institute of Geography and Statistics. Families with older adults represented 28% of all families, being smaller and having higher average income when compared to families without older adults. Older adults were head of the household in 85% of the families, with income based mainly on social protection policies. The families with older adult or couple as head of the household had significantly higher average monthly income. The proportion of out-of-pocket health expenditure per income quintile per capita was higher for families with one older adult or couple as head of the household, when compared to families without older adult as head of the household and even more in families without older adults at all. These findings allow the identification of potential positive impacts on the quality of life of families with older adults in Brazil. The higher household income of families with older adults is a consequence of the expansion of inclusive social protection policies for this population in the 2000s in Brazil, especially for families with lower average income levels, representing 4/5 of this population. The economic and political crisis in the 2010s have probably reduced these families' relative advantage, and this study will compare with results of the next survey.